Analisis Pengaruh Alokasi Penggunaan Input, Efisiensi dan Inefisiensi Terhadap Produksi Usahatani Kakao - Aras, Irmayani; Amrullah, A.; Viantika S, Ni Made (Hasanuddin University, 2025)
This study aims to analyze the influence of the use of production inputs, the level of technical efficiency, allocative efficiency and economic efficiency of input use and to analyze the factors that affect the inefficiency of cocoa farming in Marioriwawo District, Soppeng Regency. The analysis uses the Stochastic Frontier Production Function Model, Technical, Allocative and Economic Efficiency Analysis and Production Inefficiency Model. The results of the study showed that the variables of seeds, herbicides, fungicides, insecticides, fertilization labor, weeding labor and rejuvenation labor had a positive and significant effect on cocoa production, while the NPK Phonska fertilizer variable was significant but had a negative effect on cocoa production. Technically, cocoa farming is at 66% so it has the potential to increase its efficiency by 34%. Then the results of the allocative efficiency analysis showed that Seeds, Fungicides, Insecticides, Fertilization Labor and Rejuvenation Labor were not efficient while Herbicides and Weeding Labor were inefficient. Meanwhile, the value of economic efficiency was obtained at 1.0032 which shows that maximum economic efficiency has not been achieved. Furthermore, in the analysis of technical inefficiency, the variables of Farmer Age and Number of Dependents had a positive effect on technical inefficiency. Meanwhile, the variable of Length of Education has a significant negative effect on technical inefficiency.